Effects of increasing levels of dietary cation–anion difference on growth performance, nutrient digestibility, rumen fermentation, and rumen microbiota in fattening Hu sheep - Yu Wang; Wenjin Zheng; Hongwei Duan; Jiazhi Luo; Yuyang Yin; Junshi Shen; Shengyong Mao; Weiyun Zhu; Zhongtang Yu (Animal Nutrition)
The dietary cation–anion difference (DCAD) has the potential to influence the physiological functions of animals. Nonetheless, there is a notable scarcity of research in the field of ruminant science regarding its effects on fattening sheep, particularly with respect to the rumen microbiota. Therefore, this study evaluated the effects of varied DCAD levels on growth performance, rumen fermentation, and rumen bacterial communities in fattening Hu sheep. Thirty-six fattening male sheep (20.66 ± 1.53 kg) were divided into two blocks based on body weight (BW), and the sheep in each block were then randomly assigned to one of three dietary treatments: low DCAD (LD, 2.3 mEq/kg of dry matter [DM]), medium DCAD (MD, 132.1 mEq/kg of DM), and high DCAD (HD, 276.9 mEq/kg of DM). The experiment lasted for 10 weeks, with 2 weeks of adaptation and 8 weeks of measurements and sampling. This experiment found that DCAD levels did not affect dry matter intake (DMI), average daily gain (ADG), or feed conversion efficiency of gain (G:F) of fattening Hu sheep (P > 0.05). However, the high DCAD level resulted in a linear increase in the apparent digestibilities of DM, organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), and ether extract (EE) (P < 0.05). Additionally, rumen pH exhibited a linear increase (P = 0.005) with the increase in DCAD level, while the concentrations of isobutyrate, isovalerate, and total branched-chain volatile fatty acids (BCVFA) displayed quadratic effects (P < 0.05), with the MD group showing the lowest values. Blood pH (P < 0.001), HCO3- (P = 0.011), and creatinine concentrations (P = 0.004) increased linearly, whereas Cl concentration decreased linearly (P < 0.001) with the increase in DCAD level. Metataxonomic analysis indicated a trend of higher ACE, Shannon, and Chao1 indexes in the HD group compared to the LD group (0.05 < P < 0.10). Principal coordinates analysis (PCoA) showed significant differences in rumen bacterial communities among the sheep groups (P = 0.016). Proteobacteria was significantly more relative abundant in the HD group compared to the MD and the LD groups (P = 0.011). At the genus level, the Rikenellaceae RC9 gut group (P = 0.064) and the unclassified Eubacterium coprostanoligenes group (P = 0.083) showed trends towards higher relative abundances in the MD group compared to the HD group. In conclusion, within the range of 0 to 300 mEq/kg of DM, DCAD levels did not affect the growth performance in fattening Hu sheep. However, elevated DCAD levels enhanced rumen and blood buffering capacities, increased microbial diversity within the rumen, and consequently improved nutrient digestion and the acid-base balance in sheep.